The application of quantum well solar cells to thermophotovoltaics - GRIFFIN, Paul Robert (Institutional Knowledge at Singapore Management University, 1998)
We discuss the advantages of quantum well solar cells (QWSCs) for thermophotovoltaic (TPV) applications and illustrate them with InP/lnGaAs and GaInAsP/InGaAs QWSCs which were designed for other applications and have not been optimised for TPV. It is shown that an InP p-i-n solar cell with 15 lattice matched InGaAs quantum wells (QWs) in the i region has an increase in open circuit voltage (V-oc) of (1.7 +/- 0.1) times that of a control cell of InP with InGaAs in the i-region under an illuminating spectrum close to that expected from an ideal ytterbia emitter. Also, using an InGaAsP quaternary cell of band gap wavelength of 1.1 mu m with 60 InGaAs QWs under the same illuminating spectrum the current density is increased by a factor of (2.4 +/- 0.1) over that of the InP QWSC. The quaternary cell also absorbs longer wavelengths without any significant loss in V-oc. Better temperature coefficients for the former quantum well solar cell than the control cell are observed in a spectrum approximating a black body at 3000 K. Further advantages of QWs for narrow band and broad band illuminating spectra are discussed.